(untitled) (Journal of Universal Excellence, 2026)
Research Question (RV): Do organizations encourage creativity and innovation, which can have a strong impact on products and business at the same time? Purpose: Identify and analyze the assessment of the fundamental building block of the EFQM model of excellence – creativi and innovation. Make suggestions for improvment based on the findings. Method: Using a qualitative method, reviewing professional and scientific literature, using a research method with analytical analysis and extracting the essence and findings from them. Results: The results showed that organizations have a well-developed innovative and creative activity, but the trend in all evaluation components of the EFQM model of excellence is negative, so we made suggestions for improvements. Also, the assessment of the our company building block is satisfactory. All the professional literature examined llists the main activities needed to continuously improve creativty and innovation in organizations. Organization: The research has a great impact on organizations, as the assessment of the building blocks of EFQM excellence in the field of creativity and innovation provided a starting point for change. Society: With the research we want to point out that this area is very important, so it is necessary to invest a lot in it in the future, so that the fruits of creativity and innovation will always bear fruit. Originality: The contribution of the profession is in the originality of the research. We have not yet seen research on promoting creativity and innovation displayed through the building blocks of EFQM excellence. Limitations / further research: The survery is limited to only one building block with seven EFQM substructures. It would make sense to make comparative analyzes of different companies. The impact of creativity and innovation on productivity in an organization could be examined below. organizations.